2007
DOI: 10.1111/j.1439-0329.2007.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryphonectria parasitica in Portugal: diversity of vegetative compatibility types, mating types, and occurrence of hypovirulence

Abstract: Summary Cryphonectria parasitica, the causal agent of chestnut blight, has been responsible for the decline in chestnut in Portugal for the last two decades. In order to improve understanding of C. parasitica diversity, a total of 617 isolates from all affected chestnut‐growing areas in continental Portugal, Madeira and the Azores archipelagos were studied. Nine vegetative compatibility (vc) types were identified among the isolates. EU‐11 was the most widespread vc type comprising 80.2% of the isolates, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 33 publications
3
60
0
7
Order By: Relevance
“…However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009). The studies in the Atlantic part of Europe were performed with phenotypic markers for which the genetic determinants have not been completely elucidated (that is vegetative compatible (vc) types; Robin et al, 2000;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009) or with molecular markers, but for a low number of sampled populations (Breuillin et al, 2006). Consequently, they have precluded any robust conclusions about the level of genetic relatedness among C. parasitica isolates, especially relative to Italian isolates, and on recombination processes in Western Europe.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009). The studies in the Atlantic part of Europe were performed with phenotypic markers for which the genetic determinants have not been completely elucidated (that is vegetative compatible (vc) types; Robin et al, 2000;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009) or with molecular markers, but for a low number of sampled populations (Breuillin et al, 2006). Consequently, they have precluded any robust conclusions about the level of genetic relatedness among C. parasitica isolates, especially relative to Italian isolates, and on recombination processes in Western Europe.…”
Section: Introductionmentioning
confidence: 97%
“…In both continents, the genetic diversity of C. parasitica populations seemed lower than in Japan and China, the native area of C. parasitica (for example Liu and Milgroom, 2007). Although the recent analysis of South-Eastern European populations showed a clonal expansion of C. parasitica likely from Italy (Milgroom et al, 2008), genetic analyses of populations from the Atlantic part of Europe suggested that other populations genetically divergent from Italian populations could have been introduced and would spread clonally (Breuillin et al, 2006;Braganca et al, 2007;Montenegro et al, 2008;Robin et al, 2009). However, in contrast to Eastern European populations in which only one mating was generally detected (Milgroom et al, 2008), in these Western populations both mating types were often found allowing sexual reproduction among isolates in this heterothallic haploid species (Braganca et al, 2007;Dutech et al, 2008;Robin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial extensive surveys in that region, from 115 different sites in 20 different communities and around 10,000 inspected trees, had revealed 8-10% of blighted trees with varied disease incidence among sites and communities (Gouveia et al, 2001). Recent surveys in areas where the disease was previously recognised have revealed an increase in disease incidence with 40-100% of infected trees (Bragança et al, 2007) which together with the large number of new infected sites greatly increase losses in chestnut fruit production and lead to decline and death of many chestnut trees.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, after two decades of chestnut blight introduction, hypovirulence is not currently frequent. Despite the fact that some isolates have shown reduced levels of pigmentation and sporulation on PDA and some cankers seemed to be healing cankers, only one isolate of C. parasitica was identified until now in Portugal as CHV infected (Bragança et al, 2007). The population of C. parasitica in Portugal is characterized by general low vc type diversity (Bragança et al, 2007) and in the northeast many sub-populations have only one vc type (Gouveia et al, 2001).…”
mentioning
confidence: 99%